Analysis of stochastic models of identification clouds - Balys, Vaidas; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2005)
This paper deals with problem of automatic keywords assignment for scientific publications. In recent papers proposed identification clouds based classification algorithms are analysed and compared to popular alternavite methods. The efficiency of algorithms is estimated through real data based experiments. Conclusions about practical aspects and applicability of proposed algorithms are drawn.
Keywords: identification clouds; keywords; classification algorithms